Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1517/17425255.2012.652615
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of alteplase in the treatment of ischaemic stroke

Abstract: The pharmacokinetic profile of alteplase is almost entirely derived from studies in AMI. Differences in the pathophysiology of AMI and AIS mean it cannot be assumed that the pharmacokinetics of alteplase is similar in these two populations. During AMI, cardiac function and, hence, hepatic perfusion and clearance of alteplase may be impaired. The relatively older population in AIS may have impaired metabolic clearance which may increase plasma concentrations. The concurrent use of medications such as nitrates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 73 publications
(64 reference statements)
1
36
0
Order By: Relevance
“…This interaction between t-PA and the BBB may contribute to bleeding complications associated with t-PA-induced thrombolysis 4,34,35 and is thus a subject for current research efforts. Our studies in vitro confirmed that t-PA indeed increased the permeability of the intact BBB in a concentration-( Figure 4A) and time-dependent manner (Figure 4B), which were both within a pharmacologically-relevant range 36,37 . Furthermore, dramatic morphological changes of SVG astrocytes could be observed on the porous membranes post exposure to t-PA ( Figure 4C), suggesting that astrocytic responses to t-PA underlie t-PA-induced BBB opening.…”
Section: Representative Resultssupporting
confidence: 73%
“…This interaction between t-PA and the BBB may contribute to bleeding complications associated with t-PA-induced thrombolysis 4,34,35 and is thus a subject for current research efforts. Our studies in vitro confirmed that t-PA indeed increased the permeability of the intact BBB in a concentration-( Figure 4A) and time-dependent manner (Figure 4B), which were both within a pharmacologically-relevant range 36,37 . Furthermore, dramatic morphological changes of SVG astrocytes could be observed on the porous membranes post exposure to t-PA ( Figure 4C), suggesting that astrocytic responses to t-PA underlie t-PA-induced BBB opening.…”
Section: Representative Resultssupporting
confidence: 73%
“…20,21 For example, the therapeutic use of plasminogen activators to treat embolic stroke 22 and heart attack 23 may be complicated by the novel discovery of plasmin-mediated inhibition of FXIII-A 2 *. Physiologically, tPA is present in the blood at ;70 pM; however, therapeutic tPA is typically administered either IV, leading to systemic blood concentrations of ;50 nM, 24 or locally into clots from intravascular catheters at ;400 nM. 19 In our experiments, FXIII-A 2 * was degraded during clot formation under thrombolytic conditions, at 50 nM tPA.…”
Section: Discussionmentioning
confidence: 73%
“…As for pharmacokinetics, a dose-dependent effect of alteplase on stroke outcome has been shown in different studies with significant higher rates of ICH rate with doses above 0.95 mg/kg, which has led to a licensed dose for administration of 0.9 mg/kg body weight [16]. The drug is predominantly metabolized by the liver and is eliminated via urine [16], as is ceftriaxone [17]. However, to date no data comparing both pharmacokinetic profiles have been published.…”
Section: Discussionmentioning
confidence: 99%